2017
DOI: 10.1287/trsc.2015.0659
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Potential Market for Electric Vehicles

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 38 publications
0
39
0
3
Order By: Relevance
“…They conclude that the Renault BEVs have a stronger potential that the conventional Renault cars. Jensen et al (2014) add to the hybrid model a diffusion model in Table 1 Overview of selected SP studies on consumer preferences and market penetration of AFVs. year, a higher increase is seen each year.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They conclude that the Renault BEVs have a stronger potential that the conventional Renault cars. Jensen et al (2014) add to the hybrid model a diffusion model in Table 1 Overview of selected SP studies on consumer preferences and market penetration of AFVs. year, a higher increase is seen each year.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of these studies (e.g., Bunch, Bradley, Golob, Kitamura, & Occhiuzzo, 1993;Batley, Knight, & Toner, 2004;Horne, Jaccard, & Tiedemann, 2005;Potoglou & Kanaroglou, 2007;Mabit & Fosgerau, 2011;Achtnicht, 2012;Daziano & Bolduc, 2013;Hackbarth & Madlener, 2013) analyzed the effect of car features (such as purchase price, driving range, fuel costs) and charging location (Batley et al, 2004;Bockarjova, Rietveld, & Knockaert, 2013;Ito, Takeuchi, & Managi, 2013;Jensen, Cherchi, Mabit, & Ortuzar, 2014) on the AFV's demand. Some recent studies have also explored the role of individuals' attitudes, mainly toward environment sensitivity (Daziano & Chiew, 2012;Daziano & Bolduc, 2013;Jensen, Cherchi, & Mabit, 2013;Glerum, Stankovikj, Themans, & Bierlaire, 2013) but also toward car features (Mabit & Fosgerau 2011), in their propensity to buy AFVs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the characteristics of EVs and their recharging options play crucial roles in explaining their potential demand, some authors (Struben & Sterman, 2008;Shephard, Bonsall, & Harrison, 2012;Jensen et al, 2014) have recently shown that the diffusion effect can be one of the reasons behind the delay of EV market penetration. The diffusion effect refers to the time delay in adopting an innovative product because that an innovation is first adopted by a (usually initially small) segment of individuals, while the majority of the people delay their choice until the product will be widespread in the market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have analyzed the marginal effect of vehicle attributes, such as price and driving range, on ICEV and BEV user values by modeling consumer choice behaviors and demand for the automobile market among existing products 18‐25 . However, it is problematic to assess how design changes and technological improvements in the near and long term affect the ICEV and BEV user values if one only considers demand‐side empirical models.…”
Section: Introductionmentioning
confidence: 99%